Common coding and dynamic interactions between observed, imagined, and experienced motor and somatosensory activity. (December 2015) - Case, Laura K.; Pineda, Jaime; Ramachandran, Vilayanur S.
Abstract: Motor imagery and perception – considered generally as forms of motor simulation – share overlapping neural representations with motor production. While much research has focused on the extent of this "common coding, " less attention has been paid to how these overlapping representations interact. How do imagined, observed, or produced actions influence one another, and how do we maintain control over our perception and behavior? In the first part of this review we describe interactions between motor production and motor simulation, and explore apparent regulatory mechanisms that balance these processes. Next, we consider the somatosensory system. Numerous studies now support a "sensory mirror system" comprised of neural representations activated by either afferent sensation or vicarious sensation. In the second part of this review we summarize evidence for shared representations of sensation and sensory simulation (including imagery and observed sensation), and suggest that similar interactions and regulation of simulation occur in the somatosensory domain as in the motor domain. We suggest that both motor and somatosensory simulations are flexibly regulated to support simulations congruent with our sensorimotor experience and goals and suppress or separate the influence of those that are not. These regulatory mechanisms are frequently revealed by cases of brain injury but can also be employed to facilitate sensorimotor rehabilitation. Highlights: Motor imagery, observed action, and motor production show strong neural overlap. Somatosensory imagery, observed touch, and somatosensation also show overlap. Simulation (imagery and observation), perception, and action influence one another. Numerous brain areas regulate influence of simulation on action and perception. Deafferentation and brain injury demonstrate dynamic regulation of simulation.